Sustainability index analysis of the black soldier fly (Hermetia illucens) cultivation from food waste substrate - A.D. Santoso; T. Handayani; R.A. Nugroho; A.I. Yanuar; N. Nadirah; E.S. Rohaeni; E. Widjaja; M.A.M. Oktaufik; U. Ayuningtyas; Y.P. Erlambang; R. Herdioso; M.N. Rofiq; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Most food waste is dominated by domestic activities consisting of large numbers of organic pollutants, such as nitrogen and phosphate potentially hazardous to the environment. Domestic waste can be used as a feed source in black soldier fly cultivation with utility in pollutant removal, animal feed production, and compost fertilizer. Therefore, this study aimed to determine sustainability of larvae from black soldier fly cultivation by calculating and analyzing index.METHODS: Data collection was conducted using the scientific judgment of experts and business actors in black soldier fly through Focus Group Discussion and the filling out of questionnaires consisting of 31 attributes connected with environment or ecology, economics, social, and technology dimensions. Furthermore, the data were calculated using the multi-dimensional scale approach with rapid appraisal software. Sustainability status and leverage attributes were analyzed by Monte Carlo analysis, and alternating least-squares algorithm.FINDINGS: Sustainability index for larvae of black soldier fly production was 89.69 percent. The result suggested that the technique in several stages of operation including waste collection, cultivation, harvesting, and commercialization contributed to sustainability development when the elements of strength of each dimension are considered. From the analysis of the four dimensions, economic dimension had 100 percent or maximum leverage value. The environmental and social dimensions had the same leverage values of 92.02 percent, while the technological dimension had 74.74 percent. The results indicated that management experiences and techniques, potential for odor generated, family member involvement, productivity level, and managers level, warrant further attention to improve sustainability of black soldier fly production.CONCLUSION: Production, productivity, land conversion, and population were identified as significant or dominating factors impacting the supply framework of black soldier fly production by the intended investigation inside the display ponders. Therefore, study should be encouraged to effectively integrate black soldier fly biomass as a value-added component in an ideal environmental, social, economic, and technical system. The results are significant in providing insights into the possibility of feasible black soldier fly biomass production in Indonesia, which can inform government policies and programs.